Palaeoproterozoic I-type granodiorites of the Lunevsky massif, Kursk Block, Sarmatia: U-Pb age, isotopic systematics and sources of melt (Proceedings of Voronezh State University. Series: Geology, 2021)
Introduction: Recently age dating and isotope-geochemical data for the rocks of the Kursk Block allow for completely revision of the crustal growth history of Eastern Sarmatia in the Early Precambrian. However, there are very few data on the age, isotopic and elemental geochemistry of granodiorite-diorite massifs that are the most extensive manifestation of the Palaeoproterozoic magmatic event in the Kursk Block. This study contributes to the solution of this problem and is devoted to the Lunevsky massif of granodiorites. In the study, we focused on the Lunevsky granodiotite massif to contribute to the solution of the age crystallization and sources of melts on the basis of their geochemical study, U-Pb, Lu-Hf, and Sm-Nd isotope systematics. Methodology: We carried out geochemical, U-Pb, Lu-Hf, and Sm-Nd studies of rocks from the Lunevksry massif to determine the age of formation and sources of melts of the granodiorites. Results and discussion: In terms of mineral composition and geochemical characteristics, the granodiorites of the Lunevsky massif belong to I-type granitoids and have adakite signatures. The crystallization age of the massif is 2040 Ma. It has a post-tectonic position. Conclusion: The Hf isotopic composition in zircon indicates the participation of several sources in the formation of granodiorite melt, including crustal Paleoarchean and juvenile mantle Paleoproterozoic protoliths.
Keywords: Kursk Block; Paleoproterozoic; granodiorites; U-Pb isotopic age; melt sources; isotope systematics